DAPATKAH STATUS UNSUR HARA DAN PRODUKTIVITAS TANAMAN PADI METODE SRI (SYSTEM OF RICE INTENSIFICATION) DITINGKATKAN? - Virgus Amin Nugroho; Cahyo Prayogo (Jurnal Tanah dan Sumberdaya Lahan, 2016)
Based on data from Malang District in 2015, Pakisaji has the potential to reach 17,000 tons of rice yield. However, it has some hindrance in water availability that affects rice planting planted using conventional methods. One of the rice cropping system that can be used to reduce water usage is SRI (System of Rice Intensification) method. The goal of this study was to know the content change ofÂ  soil N, P, K due to application of NPK 15-15-15 fertilizer combined with biofertilizer using SRI method and determine the level of crop production. The results of this study showed that the application of NPK 15-15-15 fertilizer combined with biofertilizer in SRI method produced the highest soil nutrient content such as total nitrogen (0.29%), P availability (26.31 ppm), and K availability (0.58 me 100 g-1 especially at the depth of 0-20 cm. The combination of NPK 15-15-15 fertilizer and biofertilizer applied in SRI method obtained the highest yield at a weight of 1000 seeds (30.31 g) and yield of dry grain harvest (8.4 t ha-1).